Characteristics and Genesis of Heavy Oil in Shallow and Thin Layers in Chepaizi Area, Xinjiang, China - Jianqiang Tao; Chunyu Hu; Wenfeng Wang; Xiangquan Gao; Shuo Feng; Changcheng Han; Jiapeng Zhang (Energies)
The Neoproterozoic Shawan Formation in the Chepaizi area is recognized for its significant heavy oil resources. Investigating the underlying causes and mechanisms of heavy oil changes in accordance with the specific characteristics of the reservoir is crucial for future exploration and development. The distribution of heavy oil in the Pai 612 block was identified to present a combination of shallow and thin deposits, high porosity, high permeability, and elevated water content. The physicochemical properties of the crude oil included a complex composition, high density, high viscosity, substantial gel content, and notable oxidation-biodegradation potential. The oxidation and biodegradation of crude oil during transportation played the critical roles in the formation of heavy oil. As cru3de oil was transported upward, the formation temperature decreased, resulting in increased viscosity. An excess of water could initially increase and subsequently decrease heavy oil viscosity, while groundwater in the reservoir contained various chemicals that interacted with colloids and asphaltenes, further increasing the viscosity. During the formation of the early heavy oil reservoir, the light oil was unable to dissolve and transport the high-molecular-weight asphaltene component, leading to the high resin content in the heavy oil of the Pai 612 block.